Fostering self-care and quality of life of preachers using cognitive behavioral therapy - Diamante, Jann Dirk A.
This study examined the effectiveness of Cognitive Behavioral Therapy (CBT) as a counseling approach to improve self-care practices and the professional quality of life of preachers. Many church members think of preachers as superheroes (Samushonga, 2020) who, at a moment's notice, would drop everything to comfort and relieve those that need a helping hand. However, the preachers themselves were derelict in caring for themselves. They were called to the ministry of helps while also needing help (Lockwood, 2020). Using the Convergent Mixed Method, quantitative and qualitative data were collected simultaneously, analyzed separately, and integrated carefully. With purposive sampling, seven participants were chosen based on the initial Professional Quality of Life (ProQOL) scores. The ProQOL questionnaire measured Compassion Satisfaction (CS) and Compassion Fatigue (CF). The latter has two components, Burnout and Secondary Traumatic Stress. After six individual therapy sessions, all the qualified participants were each given a posttest to determine if CBT effected changes in their lives. Results showed that preachers perceived self-care as the ability to set goals and priorities that promote and improve one's health. They also believed that self-care was the process of finding balance so that they can allot time for themselves while scheduling meaningful events with family, loved ones and friends, engaging in the demands of work and in dealing with the expectations of society and involvement in various activities that promote well-being. Wilcoxon Signed-Rank Score was used, and changes were evident in the posttest scores of all seven preachers after their exposure to CBT. Compassion Satisfaction increased, while the components of Compassion Fatigue, Burnout and Secondary Traumatic Stress, decreased. It was recommended that CBT be used in responsive programs to improve self-care and the quality of life of preachers.